Analysis of RNA-binding proteins by in vitro genetic selection: identification of an amino acid residue important for locking U1A onto its RNA target. - Laird-Offringa, I A (1995)
An in vitro genetic system was developed as a rapid means for studying the specificity determinants of RNA-binding proteins. This system was used to investigate the origin of the RNA-binding specificity of the mammalian spliceosomal protein U1A. The U1A domain responsible for binding to U1 small nuclear RNA was locally mutagenized and displayed as a combinatorial library on filamentous bacteriophage. Affinity selection identified four U1A residues in the mutagenized region that are important for specific binding to U1 hairpin II. One of these residues (Leu-49) disproportionately affects the rates of binding and release and appears to play a critical role in locking the protein onto the RNA. Interestingly, a protein variant that binds more tightly than U1A emerged during the selection, showing that the affinity of U1A for U1 RNA has not been optimized during evolution.